Status of a Critically Endangered Medicinal and Aromatic Herbs Nardostachys jatamansi DC. in Alpine Meadows of Nepal - Joshi, Nabin Raj (NPRC Journal of Multidisciplinary Research, 2026)
Background: The Himalayan endemic and critically endangered Nardostachys jatamansi DC (Jatamansi), a highly prized medicinal and aromatic plant, is of great ecological, cultural, and socioeconomic significance. However, overharvesting, habitat degradation, and climate-induced range shifts are rapidly threatening its wild populations, necessitating robust ecological and management evidence at community forest levels.Methods: This study conducted a comprehensive ecological assessment across the high-altitude Community Forest User Groups in 5 districts. Data were collected from nested sample plots supported by participatory resource mapping. Growing stock, population density, regeneration status, and annual allowable harvest (AAH) were estimated. Trade trends and traditional uses were assessed through interviews and secondary data review.Results:  The average dry rhizome growing stock ranged from 39.9 to 295 kg ha⁻¹, while mature plant density varied between 195 and 999 individuals ha⁻¹ and regeneration density between 139 and 1,066 individuals ha⁻¹. Mugu district exhibited comparatively stronger populations. Despite frequent over extraction beyond sustainable levels, Higher production in terms of growing stock was associated with north-facing slopes, peak productivity occurred in 3,700–3,900 m as it represents a unique and significant productive niche. Ethnobotanical surveys documented 27 traditional uses, particularly for mental health, ritual purification, and cardiovascular ailments.Conclusion: Findings of this study indicates the urgency of development of the species-specific sustainable harvesting guidelines, community-based monitoring & traceable system.Novelty: This study integrates ecological inventory, ethnobotany, and harvest estimation at CFUG level, providing rare field-based evidence for sustainable management of N. jatamansi in Nepal’s alpine ecosystems.